Propaganda władz PRL wobec drugiej wizyty Jana Pawła II na przykładzie , Gazety Krakowskiej” - Łatka, Rafał (Komunizm: System - Ludzie - Dokumentacja, 2013)
Article presents one of the most important problems connected with the pilgrimages of Jean Paul II in the Polish People Republic- press propaganda. Author described the main purposes of communist government and how it was realized in practice, on example of the magazine of Cracow Commitee of Polish United Worker’s Party.